Translation and Psychometric Properties of a Spanish Version of the College Alcohol Problems Scale - McCabe, Brian E. (Addict Behav, 2017)
Hispanic and Spanish-speaking college students are under-represented in alcohol intervention and prevention research. There is a need for brief, empirically validated Spanish versions of measures related to alcohol use and consequences. The objective of this study was to translate the 8-item College Alcohol Problems Scale (CAPS) into Spanish and evaluate the psychometric properties of this measure compared to the original English. Bilingual experts in interventions for Hispanic college students and youth used a translation back-translation process. 125 Hispanic undergraduate students from a large southeastern public university completed the CAPS and a heavy drinking measure in Spanish. The two-factor model had acceptable model fit in Spanish, χ(2) (df = 19) = 27.60, p = .091; CFI = .966; RMSEA = .060. Internal consistency of the personal problems subscale was .76, and the social problems subscale was .73. The two latent factors explained 24 – 66% of variability in items. Personal problems and social problems were both significantly correlated with heavy drinking, r = .61, p < .001, r = .59, p < .001, respectively. This Spanish version of the CAPS is a reliable and valid measure of consequences of alcohol use, and has similar psychometric properties to the original English version. This measure may be useful for future research, intervention, and prevention with samples of U.S. Hispanic college students or Spanish-speaking students in other nations.